The Psychometric Parameters of the Farsi Form of the Arabic Scale of Death Anxiety. (18th June 2017) - Dadfar, Mahboubeh; Abdel-Khalek, Ahmed M.; Lester, David; Atef Vahid, Mohammad Kazem
Abstract : The aim of this study was to describe the psychometric properties of the Farsi Form of the Arabic Scale of Death Anxiety (ASDA). The original scale was first translated into Farsi by language experts using the back translation procedure and then administered to a total of 252 Iranian college students and 52 psychiatric outpatients from psychiatric and psychological clinics. The one-week test-retest reliability of the Farsi version in a sample of college students was 0.78, indicating good temporal stability and corroborating the trait-like nature of scores. Cronbach'sα was 0.90 for the college students and 0.92 for the psychiatric outpatients, indicating high internal consistency. Scale scores correlated 0.46 with Death Obsession Scale scores, 0.56 with Death Depression Scale scores, 0.41 with Death Anxiety Scale scores, and 0.40 with Wish to be Dead Scale scores, indicating good construct and criterion-related validity. A principal component analysis with a Varimax rotation yielded four factors in the sample of Iranian college students, indicating a lack of homogeneity in the content of the scale. Male students obtained a significant higher mean score than did females. It was concluded that the Farsi ASDA had good internal consistency, temporal stability, criterion-related validity, and a factor structure reflecting important features of death anxiety. In general, the Farsi ASDA could be recommended for use in research on death anxiety among Iranian college students and psychiatric outpatients.